The Influence of Marketing Strategy, Accessibility, and Tourism Support Infrastructure on Foreign Tourist Satisfaction in Bali, Indonesia - Santi Diwyarthi, Ni Desak Made; Citrawati, Luh Putu; Darmiati, Made; Mas Wiartha, Nyoman Gede; Kusumarini, Indah; Adi Pratama, I Wayan; Jata, I Wayan (West Science Interdisciplinary Studies, 2024)
This study investigates the effect of marketing strategy, accessibility, and tourism support infrastructure on foreign tourist satisfaction in Bali, Indonesia. Utilizing a quantitative approach, data was collected from 200 foreign tourists through structured questionnaires, employing a Likert scale ranging from 1 to 5. The data was analyzed using SPSS 26 software. The findings reveal that all hypotheses are positive and significant, indicating that effective marketing strategies, improved accessibility, and robust tourism support infrastructure substantially enhance foreign tourist satisfaction. These results underscore the importance of strategic marketing, accessible facilities, and comprehensive infrastructure in promoting tourist satisfaction and sustaining Bali's tourism industry. This study provides valuable insights for policymakers and stakeholders aiming to boost Bali's attractiveness as a global tourist destination.